The multifaceted implications and challenges of relocating Indonesia’s capital city: A comprehensive review of socio-economic, environmental, urban planning, and policy considerations - Hilal, Najm Al-Deen Moneer; Komariah Komariah; Ramelan, Ari Handono (Sustinere (Online), 2024)
Indonesia's planned relocation of its capital city from Jakarta to Nusantara in East Kalimantan represents a multifaceted and ambitious undertaking with far-reaching implications. This study conducts a comprehensive review of the socio-economic, environmental, urban planning, and policy considerations associated with this project. Through a thematic analysis of 19 relevant studies published between 2015 and 2023, the research explores the potential benefits and challenges of the relocation. The findings highlight several potential benefits, such as a more equitable distribution of national welfare, economic growth, and environmental improvement driven by the development of a forest city concept. However, the study also raisee concerns about possible negative impacts on the real estate industry in Greater Jakarta, environmental consequences such as deforestation and biodiversity loss, and the need for social and cultural adaptation among both migrating government officials and local communities. The study emphasizes the importance of adopting sustainable development practices, inclusive development strategies, and effective governance frameworks to ensure a successful and sustainable transition to the new capital city. Additionally, it identifies research gaps, particularly regarding the long-term impacts on various sectors and the effectiveness of proposed mitigation strategies. This review serves as a valuable resource for policymakers, researchers, and stakeholders involved in the IKN relocation project. It provides critical insights into the potential opportunities and challenges, emphasizing the necessity of careful planning, stakeholder engagement, and transparent implementation to achieve long-term sustainability, social equity, and equitable development.